Concluding thoughts on applying critical discourse analysis to classrooms. Issue 2 (2nd April 2020) - Wallace, Catherine
ABSTRACT: Classroom discourse is an interdisciplinary area of study that contributes to multiple domains of knowledge, including pedagogy, teacher training, second language acquisition, and communities of practice, to name a few. As classroom discourse continues to grow and evolve, so too have the approaches used by scholars to investigate the discourse in classroom discourse. The current special issue represents one of several noteworthy approaches to discourse that continues to make an impact in the literature. Namely, contributors to the special issue consider why it is important to take a critical perspective beyond the interests of the micro discursive features of teaching and learning. Collectively, the contributions make connections between the teaching and learning that occurs within a classroom space and wider societal factors that come to shape such discourses.